Clinical and Genetic Analysis in Neurological Wilson’s Disease Patients With Neurological Worsening Following Chelator Therapy - Hou, Haiman; Chen, Dingbang; Liu, Junxiu; Feng, Li; Zhang, Jiwei; Liang, Xiuling; Xu, Yuming; Li, Xunhua (Frontiers in Genetics, 2022)
Objectives: None of the previous studies have focused on the genetic effect on neurological worsening in neurological Wilson’s disease (WD) patients following chelator therapy. We aimed to evaluate the clinical and genetic role in the occurrence of neurological worsening. Methods: We retrospectively reviewed the medical records of neurological WD patients who received initial chelator therapy and genetic test. Clinical, laboratory, and genetic data were collected. The genotype was classified into two types: 1) severe mutation genotype: patients who carried at least one of the following three types of mutations: frameshift mutation, splicing mutation, or nonsense mutation; 2) non-severe mutation genotype: patients who only carried missense mutations. Then, the clinical features and genotype of the patients with and without neurological worsening were investigated. Results: Forty-seven neurological WD patients were identified with a median age at onset of 16.17 years (range 7.75-47 years) and 35 (74.5%) males. The mean interval from onset to diagnosis was 0.6 years (range: 0.5 months-6.25 years). Neurological deterioration was observed in 29 patients (61.7%) and the other 18 patients (38.3%) were stable or improved during anti-copper treatment. The neurological worsening was completely irreversible in 6 cases (20.7%) and partially irreversible in 16 cases (55.2%). The common deteriorated symptoms were as follows: rigidity in 20 cases (69%), speech difficulties in 20 cases (69%)), walking difficulties in 13 cases (44.8%), dysphagia in 9 cases (31%), and salivation in 9 cases (31%). The patients with neurological worsening had significantly younger age (p = 0.028), shorter delayed diagnosis time (p = 0.011), higher rate of dystonia (p = 0.003), and severe mutation genotype (p = 0.036), compared to those without neurological worsening. Conclusions: We found that younger age of onset, the presence of dystonia, and genotype with severe mutations may be predictive of neurological worsening in the neurological WD patients that received chelator therapy. For those patients, chelator therapy should be given with caution and needs closer observation during follow-up.